Motivation of Housewives to Attend Learning Activity at the Darrurahmah Ta'lim Assembly, Village 16 Ulu, Palembang - Zakira, Thalitha; Andriani, Dian Sri; Shomedran, Shomedran (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
This research aims to determine the motivation of housewives to take part in recitation at the Darrurahmah Ta'lim Assembly, Subdistrict 16 Ulu Palembang, seen from two aspects of motivation, namely intrinsic and extrinsic aspects. This research is descriptive research with a qualitative approach. This research data collection used observation, interview and documentation methods. The subjects in this research were the recitation congregation at the Darrurahmah Ta'lim Assembly, Subdistrict 16 Ulu Palembang. The qualitative approach used was to collect data about the motivation of housewives to attend recitation regularly at Darrurahmah Ta’lim Assembly, Subdistrict 16 Ulu Palembang, while descriptive research was used to interpret the results of research that the author had conducted with informants regarding the motivation of housewives to attend recitation regularly. at the Darrurahmah Ta'lim Assembly, Subdistrict 16 Ulu Palembang. The data analysis techniques used in this research are data reduction, data display, and conclusions. The data analysis process in this research was carried out simultaneously with the data collection process. This research found that there are two aspects that encourage housewives to take part in recitation at the Darrurahmah Ta'lim Assembly, namely intrinsic and extrinsic aspects. There are two intrinsic indicators, namely achievement and progress in life level, and there are two extrinsic indicators, namely relationships between people and environmental conditions. However, there are no indicators of recognition for the intrinsic aspect and indicators of reward for the extrinsic aspect of housewives attending recitation at the Darrurahmah Ta'lim Assembly, Subdistrict 16 Ulu Palembang. The results of this research are in line with the two-factor motivation theory proposed by Herzberg, namely the intrinsic aspect consisting of indicators of achievement, recognition and progress in life level. Extrinsic aspects consist of indicators of relationships between people, rewards, and environmental conditions.